The drivers, success factors, and inhibitors of the internet of things (IoT) in office buildings - Mamoojee, Zahir (University of the Witwatersrand, Johannesburg, 2023)
IoT adoption in office buildings was accelerating as a result of growing demands placed on real estate providers to improve the quality of their spaces, amongst other factors. Deployments of IoT projects were experiencing high failure rates, which posed a challenge to organisations in the form of wasted resources. Understanding success factors, inhibitors and drivers increased the likelihood of project success. This research aimed to explore the drivers, inhibitors, and success factors of IoT solution deployments in office buildings to provide those deploying solutions with information that could be incorporated into their deployments to increase the likelihood of success. The study used an adapted version of the building blocks of digital transformation theorised by Westerman to relate drivers to IoT deployments and the Technology, Organisation, Environment (TOE) framework to relate success factors and inhibitors to project outcomes. A qualitative approach was adopted, and semi-structured interviews were conducted with ten individuals with experience deploying IoT solutions in office buildings. The interviews were analysed using thematic analysis. The analysis revealed several drivers, success factors, inhibitors, and stakeholders for IoT deployments in office buildings. They also revealed that drivers were relevant to specific stakeholders, that the IoT market was still maturing, and that there were varying degrees of success experienced in deployments by participants. Those deploying IoT solutions in office buildings e buildings can use the findings to align deployments to drivers, improve delivery practices, and design more effectively to improve project outcomes
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Management in the field of Digital Business Johannesburg, 2023
Keywords: Internet of things; Solution drivers; Solution inhibitors; Success factors; Office buildings; UCTD; SDG-9: Industry, innovation and infrastructure